2009
DOI: 10.1063/1.3203258
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Properties of CaCu3Ti4−xMnxO12 Ceramics

Abstract: Structural and dielectric properties of zinc cobalt oxide ( ZnCo 2 O 4 ) ceramics AIP Conf.Enhanced piezoelectric properties of lead zirconate titanate sol-gel derived ceramics using single crystal PbZr 0.52 Ti 0.48 O 3 cubes Abstract. This paper reports the dielectric properties of the Mn doped CaCu 3 Ti 4 O 12 (CCTO) ceramics synthesized by the conventional solid-state reaction method. By partial Mn for Ti substitution, the dielectric loss was suppressed significantly while the dielectric constant (H r ) sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The similar phenomena are also reported by some other previous works [16,18], which have not mentioned the effect on dielectric loss. However, a very small Mn substitution on Ti-sites has a significant difference from the large amount of Mn substitution reported by Makcharoen et al [19]. They have reported that high permittivity (ε > 1200) and low dielectric loss (tan ı < 0.06) for CaCu 3 Ti 4−x Mn x O 12 ceramics with x = 0.24.…”
Section: Methodsmentioning
confidence: 77%
“…The similar phenomena are also reported by some other previous works [16,18], which have not mentioned the effect on dielectric loss. However, a very small Mn substitution on Ti-sites has a significant difference from the large amount of Mn substitution reported by Makcharoen et al [19]. They have reported that high permittivity (ε > 1200) and low dielectric loss (tan ı < 0.06) for CaCu 3 Ti 4−x Mn x O 12 ceramics with x = 0.24.…”
Section: Methodsmentioning
confidence: 77%